Verantwortung und Recht: 62. Junge Tagung Öffentliches Recht - Ammann, Odile; Bottega, Fiona; Bukovac, Jasmina; Lehner, Irina; Meier, Julia; Piskóty, Réka; Rausch, Caroline; Rehmann, Meret; Schneider, Lea Ina; Weder, Regina; Wilhelm, Martin (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
Public law allocates responsibility. It regulates – and sometimes fails to regulate – the responsibility of individuals towards society, the responsibility of the State towards its population, other States and the environment, and the responsibility of the present generation towards the following ones. The contributions to the conference volume analyze the concept of responsibility from various perspectives and present the legal means of structuring responsibility in a wide range of subject areas. Special emphasis is placed on current issues such as the allocation of responsibility in the environmental field and the responsibility of legal scholars.With contributions byMag. Dr. Ranjana Andrea Achleitner; Dr. Svenja Behrendt; Anna Berry; Isa Bilgen; Daniel Busche; Stella Dörenbach; Max Erdmann, M.A.; Prisca Feihle; Dr. Corina Heri, LL.M.; Benedikt Huggins; Dipl.-Jur. Madlen Karg, LL.B. (Mannheim); Dr. Romy Klimke; Lars C. Kroemer; Kaie Lemken; Antonia Paulus; Benedict Pietsch, M.A., M.Iur.; Dr. Michael von Landenberg-Roberg, LL.M. (Cambridge) and Noah Zimmermann.